Public Perception of Pharmacist’s Role during COVID-19 Outbreak in Jordan - Jarab , Anan S.; Al-Qerem, Walid; Mukattash , Tareq L.; Alqudah , Salam G.; Abu-Zaytoun, Lina; Al-Azayzih, Ahmad; Khdour , Maher (Jordan Journal of Pharmaceutical Sciences, 2022)
Background: The pandemic COVID-19 requires collaborative teamwork by all healthcare professionals including Pharmacists who could help in combating epidemic diseases by providing several pharmaceutical services. Nevertheless, public perception of pharmacist’s role in providing health service is controversial Methods: A cross-sectional web-based design validated survey of 25 items was used to explore patients’ opinion about pharmacist’s ability to provide different health services during COVID-19 pandemic. Exploratory factor analysis (EFA) was conducted to evaluate the best model for the questionnaire. The association between different demographic variables and awareness about pharmacist’s role was evaluated using Pearson correlation, Mann-Whitney u test and Kruskal–Wallis one-way analysis of variance. Results: A total of 668 persons participated in the study. The mean (SD) of the respondent questionnaire scores was 97.1 (12.6) and the possible maximum score was 115 (12.9). Higher awareness score was associated with increased age, female gender, lower educational level, living out of Amman the capital, being college or university student or being employed in medical field. Conclusion: The positive public perception toward pharmacist role shown in the present study enlighten the need to expand pharmacist role to be more engaged in providing different health services during the disaster or normal conditions.